2020
DOI: 10.1111/padm.12667
|View full text |Cite
|
Sign up to set email alerts
|

Strategic communication by regulatory agencies as a form of reputation management: A strategic agenda

Abstract: This article develops a strategic agenda concerning regulatory agencies' strategic communication in light of the reputation literature. It highlights the main strands in this literature, presents the fundamental findings discovered so far, responds to the critiques that have recently surfaced, and offers guidance about where scholarship on strategic communication might most profitably head. The critiques discussed here centre on two aspects: (i) the claim that an agency's communication choices are to some exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 72 publications
(98 reference statements)
1
52
0
1
Order By: Relevance
“…Secondly, our analysis demonstrated that insights of the blame and reputation management literature travel to the analysis of IPAs' responses to public contestation (cf. Hinterleitner and Sager 2017;Maor 2020). This finding challenges the widespread assumption that IO member states are unconstrained in shifting blame onto IOs (Gerhards et al 2009;Vasilopoulou et al 2014;Schlipphak and Treib 2017;Sommer 2020).…”
Section: Discussionmentioning
confidence: 74%
“…Secondly, our analysis demonstrated that insights of the blame and reputation management literature travel to the analysis of IPAs' responses to public contestation (cf. Hinterleitner and Sager 2017;Maor 2020). This finding challenges the widespread assumption that IO member states are unconstrained in shifting blame onto IOs (Gerhards et al 2009;Vasilopoulou et al 2014;Schlipphak and Treib 2017;Sommer 2020).…”
Section: Discussionmentioning
confidence: 74%
“…However, most of the studies analyzed in the sample consider only one type of audience per study. This finding is significant as audiences are the core of reputation, and for public organizations it is crucial to select and gauge the perceptions of their most relevant ones over time (Christensen and Gornitzka 2019; Maor 2020). In this regard, the Overman, Busuioc, and Wood's (2020) study is outstanding—they measured 13 internal and external audiences of the European Chemicals Agency.…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings have indeed related the ramifications of reputational concerns to the varying speed at which new drugs are approved (Carpenter 2002); the apportioning of funds to certain areas (Gilad 2012); the degree of an agency’s legal independence (Maor 2007); organizational task prioritization (Gilad 2015); endogenous construction of jurisdiction (Maor 2010); the extent to which regulatory errors are publicly observable (Maor 2011); the pace of regulatory enforcement (Maor and Sulitzeanu-Kenan 2013); a regulatory agency’s policy, regulatory, and scientific outputs (Krause and Douglas 2005; Maor and Sulitzeanu-Kenan 2016; Rimkuté 2018); cooperation outcomes (Busuioc 2016); regulatory enforcement (Etienne 2015; Gilad and Yogev 2012); democratic participation in an agency’s work (Moffitt 2010); accountability relations and behavior (Busuioc and Lodge 2016; 2017; Christensen and Lodge 2018); organizational politics (Blom-Hansen and Finke 2020), strategic communication (Anastasopoulos and Withford 2019; Baekkeskov 2017; Christensen and Lægreid 2015; Christensen et al 2020; Christensen and Lægreid 2020; Gilad, Maor and Bin-Nun Bloom 2015; Grøn and Salomonsen 2019; Maor 2016a; 2020; Maor, Gilad, and Ben-Nun Bloom 2013; Moschella and Pinto 2019; Müller and Braun 2021; Rimkute 2020); and the initiation of procedures against EU member states (Veer 2021).…”
Section: Relevant Literaturementioning
confidence: 99%